Methanol oxidation reaction on Pt based electrocatalysts modified ultramicroelectrode (UME): Novel electrochemical method for monitoring rate of CO adsorption - Joshi, Vrushali S.; Poudyal, Durgasha C.; Satpati, Ashis K.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2018)
Novel fast scan cyclic voltammetry (FSCV) based method has been developed to study methanol oxidation reaction on Pt nanoparticles (PtNPs) based catalysts. To support the cyclic voltammetry measurements at higher scan rates, micron-sized electrode geometries viz. PtNPs loaded on the single strand of carbon fiber (SSCF) and PtNPs decorated multiwalled carbon nanotubes (MWCNTs), loaded on commercial ultramicroelectrode (UME) have been employed. Deconvolution of the voltammograms obtained during methanol oxidation revealed three major anodic peaks. These peaks have been plausibly attributed to the electron transfer processes viz. methanol oxidation into CO/other intermediates, oxidation of these intermediates into CO2 and adsorption of un-oxidized CO on the catalyst surface. The peaks due to CO adsorption have been elucidated as a function of scan rates. The area under the peak as a function of time has been correlated to the rate of CO adsorption on these catalysts. The average rate of CO adsorption in methanol oxidation at Pt-SSCF and Pt-MWCNTs/UME are estimated to be 1.08 x 10(-8) mol cm(-2) s(-1) and 13.5 x 10(-8) mol cm(-2) s(-1) respectively. This novel method is proposed to generalize to any electrocatalysts of interest. (C) 2018 Published by Elsevier Ltd.